Correlation between Blood Activin Levels and Clinical Parameters of Type 2 Diabetes. (16th December 2012) - Wu, Hui; Wu, Michael; Chen, Yi; Allan, Carolyn A.; Phillips, David J.; Hedger, Mark P.
Abstract : Aims . Activins A and B, and their binding protein, follistatin, regulate glucose metabolism and inflammation. Consequently, their role in type 2 diabetes (T2D) was examined. Methods . Blood was taken from fasted participants (34 males; 58 females; 50–75 years) with diabetes or during an oral glucose tolerance test (OGTT). Clinical parameters were assessed, and blood assayed for activins, follistatin, and C-reactive protein. Results . Serum levels of activin A (93.3 ± 27.0 pg/mL, mean ± SD), B (81.8 ± 30.8 pg/mL), or follistatin (6.52 ± 3.15 ng/mL) were not different (P > 0.05 ) between subjects with normal OGTT (n = 39 ), impaired glucose tolerance and/or fasting glucose (n = 17 ), or T2D (n = 36 ). However, activin A and/or activin B were positively correlated with parameters of insulin resistance and T2D, including fasting glucose (P < 0.001 ), fasting insulin (P = 0.02 ), glycated hemoglobin (P = 0.003 ), and homeostasis model assessment of insulin resistance (HOMA-IR; P < 0.001 ). Follistatin was positively correlated with HOMA-IR alone (P = 0.01 ). Conclusions . These data indicate that serum measurements of activin A, B, or follistatin cannot discriminate risk for T2D in individual patients, but the activins display a positive relationship with clinical parameters of the disease.